2019
DOI: 10.3310/hta23520
|View full text |Cite
|
Sign up to set email alerts
|

Comparing alternating pressure mattresses and high-specification foam mattresses to prevent pressure ulcers in high-risk patients: the PRESSURE 2 RCT

Abstract: Background Pressure ulcers (PUs) are a burden to patients, carers and health-care providers. Specialist mattresses minimise the intensity and duration of pressure on vulnerable skin sites in at-risk patients. Primary objective Time to developing a new PU of category ≥ 2 in patients using an alternating pressure mattress (APM) compared with a high-specification foam mattress (HSFM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 87 publications
0
26
0
9
Order By: Relevance
“…Process or degree of adaptation is affected by environmental context (Humphreys and Nicol, 1998). Thermal adaptation is actively observed in free running or naturally ventilated buildings where environmental features are closer to the outdoor environment than in airconditioned buildings (de Dear and Brager, 1998;Nicol and Humphreys, 2010). The accumulation of knowledge, based on field studies, have led to the development of empirical comfort models for naturally ventilated buildings, known as the adaptive models.…”
Section: Introductionmentioning
confidence: 99%
“…Process or degree of adaptation is affected by environmental context (Humphreys and Nicol, 1998). Thermal adaptation is actively observed in free running or naturally ventilated buildings where environmental features are closer to the outdoor environment than in airconditioned buildings (de Dear and Brager, 1998;Nicol and Humphreys, 2010). The accumulation of knowledge, based on field studies, have led to the development of empirical comfort models for naturally ventilated buildings, known as the adaptive models.…”
Section: Introductionmentioning
confidence: 99%
“…(3) The use of topical preparations, as some studies have observed that locally purified omentum lipid preparations (cream, liquid, emulsion and detergent) at different concentrations (10–25%) can prevent pressure ulcer in patients with diabetes [ 89 ]. (4) The use of mattresses to minimize the intensity and duration of pressure on vulnerable skin parts of high-risk HAPU patients: an RCT study from the UK showed that alternating pressure mattresses and high-specification foam mattresses could have a preventive effect on high-risk pressure ulcer patients [ 90 ]. (5) The use of various auxiliary materials on patient undergoing vascular surgery: one study observed that the use of 5 layers of silicone foam dressings resulted in only 1 patient developing HAPU in the dressing group (The incidence of HAPU in the dressing group was 2%, in the control group was >50%, p=0.0001).…”
Section: Management Of Diabetic Footmentioning
confidence: 99%
“…1 Clinical Trials Research Unit, University of Leeds, Leeds, UK. 2 Mid Yorks Hospitals NHS Trust, Wakefield, UK. 3 Leeds Community Healthcare NHS Trust, Leeds, UK.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Background PRESSURE 2 was a randomised controlled trial (RCT), evaluating the clinical and cost-effectiveness of two types of pressure-relieving mattress frequently used in pressure ulcer prevention practice [1,2]. Alternating pressure mattresses (APMs) were compared to highspecification foam mattresses (HSFM) with patients at high risk of pressure ulcer (PU) development in acute secondary care settings in the UK.…”
mentioning
confidence: 99%